Imaginaries Of The Venezuelan Migrant From The Narratives Of A Border Community In Cúcuta, Colombia (2022)
This text addresses the phenomenon of migration of the Venezuelan population to Colombia from the narratives of inhabitants of the border area of the Corregimiento de la Parada, located in the city of Cúcuta. Through these narratives the researchers show the atavistic imaginaries about the Venezuelan migrant through fivecategories: "the borders", "friend/enemy", "good/bad", "scapegoat", "an eye for an eye, a tooth for a tooth". An interpretative methodology is used, taking symbolic interactionism as a reference, insofar as it allows us to understand the process of creation and assignment of meanings by the residents of this area. The results show violence as a method to justify xenophobic attitudes against Venezuelan migrants.